Seroepidemiological survey on pigs and cattle for novel K88 (F4)-like colonisation factor detected in human enterotoxigenic Escherichia coli. (13th December 2022) - Tanimoto, Yoshihiko; Inoue, Miyoko; Komatsu, Kana; Odani, Atsuyuki; Wada, Takayuki; Kage-Nakadai, Eriko; Nishikawa, Yoshikazu
Abstract: Enterotoxigenic Escherichia coli (ETEC) strains that express various fimbrial or nonfimbrial colonisation factors (CFs) and enterotoxins are critical causes of diarrhoeal diseases. Human ETEC serotype O169:H41 (O169) has been a representative of epidemic ETEC worldwide; the organism shows massive adherence to HEp-2 cells similar to enteroaggregative E. coli . Previously, we determined the complete sequence of the unstable virulence plasmid, pEntYN10. The plasmid included a unique set of genes encoding a novel CF resembling K88 (F4) of porcine ETEC, in addition to CS6, a well-known representative CF of human ETEC, and another novel CF similar to CS8 (CFA/III) of human ETEC. In the present study, we focused on K88-like CF (hereafter, K88O169 ) that may allow the organisms to infect domestic livestock like original K88-harbouring strains that can cause diarrhoea in piglets. Samples were tested for antibodies against recombinant proteins of possible paralogous adhesins, FaeG1 and FaeG2, from K88O169 and the FaeG of typical K88 (F4). The seroepidemiological study using recombinant antigens (two paralogs FaeG1 and FaeG2 from K88O169 ) showed reactivity of porcine (18.0%) and bovine (17.1%) sera to K88O169 FaeG1 and/or FaeG2 antigens on indirect ELISA tests. These results suggest that E. coli with K88O169 adhesin can infect various hosts, including pigs and cattle. This is the first report of domestic livestock having antibodies to K88O169 of human ETEC. Although human ETEC had been thought to be distinguished from those of domestic animals based on CFs, zoonotic strains may conceal themselves among human ETEC organisms. The concept of One Health should be adopted to intervene in ETEC infections among animals and humans.